Itinéraires d'égalités. Trajectoires des femmes autochtones du Québec et du Canada - Levesque, Carole; Labrecque, Marie France (2007)
À l’occasion du 30e anniversaire de l’Association des Femmes autochtones du Québec, ces actes de colloque proposent de revoir le parcours des femmes autochtones dans leurs luttes pour l’égalité et la justice sociale.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; cours; discipline; droits des femmes*; environnement; féminisme autochtone; histoire et politique; inégalités; justice sociale; mexique; militance; pol4105; premier cycle; pédagogie; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; système colonial; systèmes d'oppressions; thématiques; violences; études autochtones

Introduction to "Indigenous Women: The State of Our Nations."(Canada)(Editorial) - Lawrence, Bonita; Anderson, Kim (Atlantis, 2005)
Introduction to the issue 29, 2 "Indigenous Women: The State of Our Nations".
Keywords: approches et analyses; cours; discipline; féminisme autochtone; histoire et politique; pol4105; premier cycle; sciences humaines; sciences sociales; thématiques

The fourth world: an indigenous perspective on feminism and aboriginal women's activism - Ouellette, Grace Josephine Mildred Wuttunee (Fernwood Publishing, 2002)
"This book is not about feminism. Rather, feminism is the basis of the discussion, an example of how understanding oppression must consider a number of barriers. Euro-Canadian feminists rarely address the circumstances that are unique to First Nations' women, instead working with the assumption that all women are a part of a similar struggle. Ouellette attempts to confront these barriers. Throughout interviews with a number of women, she highlights the following four questions. To what extent do Aboriginal women understand experience and articulate their oppression? To what extent do colonized women perceive racism as the source of their oppression? To what extent do Aboriginal women view male domination within their own Aboriginal societies as the source of the oppression? How do Aboriginal women articulate racism and gender oppression?The author argues that there will always be a dichotomy between European and Aboriginal thought. This book makes an important contribution toward a greater understanding of Aboriginal thought and an Aboriginal perspective on society. The Fourth World theory is an integrate part of the "Circle of Life" philosophy of Aboriginal people. In keeping with oral traditions, these teachings are passed on at gatherings and in private conversations. They compromise a distinctly Aboriginal worldview."
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; cours; discipline; féminisme autochtone; histoire et politique; inégalités; pol4105; premier cycle; périodes historiques; racisme; régions géographiques; saskatchewan; sciences humaines; sciences sociales; sexisme; système colonial; systèmes d'oppressions; thématiques; études autochtones

Les femmes des Premières nations, la gouvernance et la loi sur les Indiens : recueil de rapports de recherche en matière de politique - Sayers, Judith F.; MacDonald, Kelly A.; Fiske, Jo-Anne; Newell, Melonie; George, Evelyn; Cornet, Wendy (2001)
Table de matières: Pour une participation équitable des femmes des Premières nations à la gestion des affaires publiques, Judith F. Sayers et Kelly A. MacDonald. Les femmes des Premières nations et la gouvernance : Étude sur les coutumes et les nouvelles pratiques chez les femmes de la Première nation de Lake Babine, Jo-Anne Fiske, Melonie Newell et Evelyn George. La gouvernance des Premières nations, la Loi sur les Indiens et les droits à l’égalité des femmes, Wendy Cornet.
Keywords: amériques; approches et analyses; canada; cours; discipline; droits des femmes*; droits des femmes* autochtones; féminisme autochtone; histoire et politique; inégalités; militance; pol4105; premier cycle; racisme; régions géographiques; science politique; science politique et droit; sciences humaines; sciences sociales; sexisme; système colonial; systèmes d'oppressions; thématiques; violences